Analysis of Factors Affecting the Economic Growth of the Districts/Cities of West Java Province in 2017-2021 - Wistantri, Cindy Alisa Reninda; Bintariningtyas, Selfia (KINERJA, 2023)
This research was conducted in 2022 to analyze the human development index, labor force participation rate, poverty, CO2 emissions, and the number of MSMEs on the economic growth of districts/cities in West Java province in 2017-2021. The choice of a 5-year timeframe is because, during this period, the districts/cities of West Java province have increased economic growth every year except for 2020 due to the Covid-19 pandemic. Secondary data is an annual report, so researchers do not include 2022 because it has not accumulated a one-year period. The economy of districts/cities in West Java Province is influenced by positive factors such as the Human Development Index, CO2 emissions, and an increasing number of MSMEs. However, the increase in economic growth is inseparable from the problems of increasing the poor population and the unequal labor force in each region. The panel data regression analysis method is used to align the hypothesis with the theory. Developing research that has existed before with differences in location selection and combining variables from various aspects so that differences in results become updates to the factors that influence economic growth in this study.